Conditions for the Group of Military Personnel Determine the Results of Their Activities in Combat Situations or Combat Situations - To'rayev Shavkat Mirziyoyevich; Mavlyanov Ravshanjon Tajimamatovich (Genius Journals, 2023)
This article mainly considers the conditions under which the group of military personnel will be located, as well as the results of this group's activities in specific combat situations or combat situations.
Keywords: military personnel; group; combat training or combat situation